2017
DOI: 10.1002/jgt.22179
|View full text |Cite
|
Sign up to set email alerts
|

On the number of minimal separators in graphs

Abstract: Abstract. We consider the largest number of minimal separators a graph on n vertices can have at most.-We give a new proof that this number is in O-We prove that this number is in ω (1.4521 n ), improving on the previous best lower bound of Ω(3 n/3 ) ⊆ ω(1.4422 n ). This gives also an improved lower bound on the number of potential maximal cliques in a graph. We would like to emphasize that our proofs are short, simple, and elementary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In general, a graph may have exponentially many minimal separators, and in fact there exist graphs with (3 n/3 ) minimal separators [12]. Recently, this bound was improved to (1.4457 n ) [14]. On the other hand, some graph classes have only polynomially (even linearly) many minimal separators.…”
Section: Related Workmentioning
confidence: 99%
“…In general, a graph may have exponentially many minimal separators, and in fact there exist graphs with (3 n/3 ) minimal separators [12]. Recently, this bound was improved to (1.4457 n ) [14]. On the other hand, some graph classes have only polynomially (even linearly) many minimal separators.…”
Section: Related Workmentioning
confidence: 99%
“…We denote the set of minimal separators in G by S(G). Minimal separators are a commonly studied aspect of many graph classes [6,22,26,36]. Two particularly relevant cases include the fact that chordal graphs have at most n minimal separators [26], and that ciruclar-arc graphs have at most 2n 2 − 3n minimal separators [36].…”
Section: Minimal Separatorsmentioning
confidence: 99%
“…Given this, it is important to know how many minimal separators graphs have. Gaspers and Mackenzie [19] showed that every graph with n vertices has O * (τ n ) minimal separators, where τ = 1.618 • • • is the golden ratio 2 . They showed that there is a graph with Ω(1.4422 n ) minimal separators.…”
Section: Introductionmentioning
confidence: 99%